Nature and level of organic stock in clayey oxisols under different land use, management systems - Freitas, Pedro Luiz de; Blancaneaux, Philippe; Gavinelli, Evelyne; Larrouy, Marie Christine Larré; Feller, Christian (Pesquisa Agropecuaria Brasileira, 2000)
The important role of organic matter (OM) justifies the growing interest for the identification of more efficient use and management systems for the improvement of organic stock in tropical oxisols. The objective of this work was to analyze quantitative and qualitative OM stock variations and to characterize organic compartments in a clayey Dark-Red Latosol under situations of natural savanna vegetation (CER), long-term (PAL) and degraded grasslands (PAD), and fallow conditions (PAC). These were compared with crops under conventional plowing (CCL) and zero tillage (PD). Small organic stock variation was found in surface layer of studied soils, explained by human disturbance of vegetation in CER, no residue exportation in PD and CCL, and by fallow practice in PAC. Particle-size fractionating, considering the compartments plant residues (20-2,000 µm), silt-organic (2-20 µm) and clay-organic (0-2 µm), showed differences in OM quality, when comparing similar environmental situations. Even with very weak differences, plant residues compartment was an important indicator of organic stock evolution, allowing the characterization of grassland degradation and zero-till effect, when compared with conventional system. PD has favored C stocking in organic-clayey compartment. Studied soils were distinct from other tropical clayey soils by the high C/N relationship found in 0-20 µm fraction.